ANALISIS KEUNTUNGAN USAHA KERAJINAN BAMBU KIOS ANGEL DI KELURAHAN KINILOW KECAMATAN TOMOHON UTARA KOTA TOMOHON (Analysis of Profit of Angel Bamboo Craft Business in Kinilow Village, North Tomohon Sub District Tomohon City) - Melda Ruben Sirompo; Melsje Yellie Memah; Yolanda Pinky Ivana Rori (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to analyze the profits from the Angel Kiosk Bamboo Crafts business in the Kinilow Village, North Tomohon Sub District, Tomohon City. This research was carried out for 2 months, namely in May and June 2022. The research location was carried out at the Angel Bamboo Crafts Kiosk, Kinilow Village, North Tomohon District, Tomohon City. The data used in this study are primary data and secondary data. Primary data was obtained by using direct interview techniques with the owner (owner) of the Bamboo Crafts business using a questionnaire. Based on the processed profit data for Angel Kiosk for May 2022, a profit of Rp. 6,374,334 supported by an R/C Ratio value of 1.23 and data on the profits of Kiosk Angel for June 2022 which have been processed, a profit of Rp. 4,194,334 is supported by an R/C Ratio value of 1.20. This means Kiosk Angel gets a profit every month, but Kiosk An-gel's highest profit and R/C ratio value is in May due to the greater number of requests for lantern products in May.